US–China policy amid a persistent strategy: is conflict over Taiwan inevitable? - Nora Maher (Review of Economics and Political Science)
Purpose – This research aims to examine the US–China policy shift from Obama to Biden emphasizing the centrality of Taiwan question in the geostrategic competition with Beijing and its prospect if the US strategy remains unchanged. Design/methodology/approach – A conceptual framework is outlined, illustrating how the US grand strategy is driven by the ideological foundation of Exceptionalism. The paper highlights the associated US policy changes that evolved from Obama to Trump and then Biden to advance Washington's strategic interests in its rivalry with China over Taiwan. Findings – Biden's policy led to an escalating geopolitical competition with Beijing over Taiwan to maintain US supremacy. The Biden administration is more stringent than the previous administrations on the Taiwan question and there is the conviction that the USA must not back down on Taiwan because the alternative will be a retraction of US world primacy to Beijing. With Washington's persistent hegemonic strategy, the US–China confrontation over Taiwan seems inevitable. Originality/value – The research highlights how the Biden administration managed a perpetuated Ukraine crisis and forged unprecedented high-level ties with Taiwan, indicating the administration's determination to exacerbate contentions with Beijing over Taiwan rather than de-escalate.